2022
DOI: 10.1364/ome.463349
|View full text |Cite
|
Sign up to set email alerts
|

Fused silica as an optical material [Invited]

Abstract: Fused silica glass, with its large transparency range, low thermal expansion, high resistance to optical damage, high refractive index homogeneity, and ease of finishing has found use as an optical material in applications as varied as space shuttle windows, optical fiber, and deep UV lens elements. Its widespread role as an optical material has been enabled by manufacturing the glass from pure liquid precursor compounds, thereby minimizing impurities, and maximizing refractive index homogeneity. As a technica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 110 publications
0
17
0
Order By: Relevance
“…The choice of the ZnO layer thickness is driven by the need to obtain a compromise between a good electroacoustic transduction efficiency, easy fabrication technology (such as micro-meter sized IDTs), and low-cost production. The use of fused silica can be a good solution for many reasons: it is a low-cost substrate material which can be economically manufactured in large sizes; it has high radiation damage resistance and is transparent in the UV region [ 6 ]. Nevertheless, the ZnO/fused silica-based sensor device needs to be properly designed in terms of the type of UV illumination (from top or from back), type of wave (Rayleigh or Sezawa), electrical boundary condition (IDTs placed at the free surface of the piezoelectric layer or buried under it), and ZnO layer thickness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of the ZnO layer thickness is driven by the need to obtain a compromise between a good electroacoustic transduction efficiency, easy fabrication technology (such as micro-meter sized IDTs), and low-cost production. The use of fused silica can be a good solution for many reasons: it is a low-cost substrate material which can be economically manufactured in large sizes; it has high radiation damage resistance and is transparent in the UV region [ 6 ]. Nevertheless, the ZnO/fused silica-based sensor device needs to be properly designed in terms of the type of UV illumination (from top or from back), type of wave (Rayleigh or Sezawa), electrical boundary condition (IDTs placed at the free surface of the piezoelectric layer or buried under it), and ZnO layer thickness.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of using a transparent silica substrate in combination with the ZnO sensing layer is that the bi-layer can be illuminated by the UV light from the back (through the fused silica substrate which has a window of high transmission extending from the deep ultraviolet to the infrared region [ 6 ]) or from the top. Finite element simulations were performed which revealed that the two different sensing configurations react differently to the UV exposure and that this difference depends on the SAW mode.…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance the performance of lasers excited by Er 3+ , diverse substrate materials have been used, such as sulfide glasses, phosphate, tellurite, fluoride, and silicate [16][17][18][19]. Therein, silicate glasses offer advantages in producing low-loss microspheres and enabling laser emission at approximately 980 nm, attributed to their weak light scattering and excellent optical transparency [20].…”
Section: Introductionmentioning
confidence: 99%
“…Many experiments on LIPSS formation were performed in various glasses and in fused silica, in particular, which represents versatile and one of the most relevant optical materials, finding diverse applications in contemporary optical sciences and technology 11 . Transformation of LIPSS morphology from HSFL to LSFL was observed with the increase of number of impinging pulses 12 and laser fluence 13 , in particular demonstrating the transition from the high spatial frequency perpendicularly oriented nanoripples to the low spatial frequency ripples, parallel or perpendicular to the laser polarization 14 .…”
Section: Introductionmentioning
confidence: 99%